2019
DOI: 10.2478/bjmg-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of pentraxin 3 in placental tissues from patients with unexplained recurrent pregnancy loss

Abstract: Pentraxin 3 (PTX3), a prototypical member of the long pentraxin subfamily, is a evolutionarily conserved multimeric pattern recognition receptor involved in the humoral component of the innate immune system. Pentraxin 3 is released when tissue is stressed or damaged, and interacts with many different ligands. Pentraxin 3 exerts a pivotal role both as a regulator and as an indicator of inflammatory response in the pathogenesis of many diseases such as sepsis, vasculitis and preeclampsia. Uncontrolled inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Earlier research on PTX-3 in NETs showed that PTX-3 plays a key role in regulating the proper development of pregnancy and the inflammatory response, such as in preeclampsia. An uncontrolled inflammatory reaction is believed to be the primary cause of unexplained recurrent pregnancy loss 24 , 25 . It has been proven that the gene responsible for PTX-3 activation is activated during the early gestation period.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research on PTX-3 in NETs showed that PTX-3 plays a key role in regulating the proper development of pregnancy and the inflammatory response, such as in preeclampsia. An uncontrolled inflammatory reaction is believed to be the primary cause of unexplained recurrent pregnancy loss 24 , 25 . It has been proven that the gene responsible for PTX-3 activation is activated during the early gestation period.…”
Section: Discussionmentioning
confidence: 99%
“…15,[29][30][31][32] Additionally, the expression of PTX3 is dramatically increased in placental tissues obtained from patients with unexplained recurrent pregnancy loss. 16 Collectively, we speculate that abnormally elevated levels of PTX3 can induce an aberrant innate immune response or exaggerate an inflammatory reaction, which leads to pathological pregnancy. In this regard, studies have shown that the expression of PTX3 in human stromal cells can be upregulated by progesterone, trophoblast explants or several F I G U R E 7 Proposed model of the signaling pathway mediating BMP2-induced downregulation of Pentraxin 3 expression in human endometrial stromal cells and decidual stromal cells.…”
Section: F I G U R Ementioning
confidence: 90%
“…Recent studies have shown that PTX3 is involved in the pathogenesis of several vascular complications during pregnancy, and PTX3 levels are markedly elevated in women with preeclampsia, HELLP syndrome, intrauterine growth restriction, and pregnancy with type 1 diabetes or GDM and even in pregnant women with obesity 15,29–32 . Additionally, the expression of PTX3 is dramatically increased in placental tissues obtained from patients with unexplained recurrent pregnancy loss 16 . Collectively, we speculate that abnormally elevated levels of PTX3 can induce an aberrant innate immune response or exaggerate an inflammatory reaction, which leads to pathological pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly elevated maternal serum levels of PTX3 during in vitro embryo transfer have negative effects on embryo implantation (12) . Elevated blood PTX3 in the first trimester and in placental tissues is also associated with recurrent pregnancy loss (13,14) . Elevated maternal blood PTX3 may be considered an early marker of placental dysfunction, and it was seen in pathological pregnancies (complicated with pre-eclampsia, gestational diabetes, preterm birth, and premature rupture of membranes) (7,10,11) .…”
Section: Diagnosis Of Fertility Disorders and Pregnancy Pathologymentioning
confidence: 99%